Yoga for children & young people with autism : yoga games and activities to engage everyone across the spectrum - Chissick, Michael, ....-; Peacock, Sarah, ....- (London ; : Jessica Kingsley Publishers, 2019)
Speaking from decades of experience, Michael Chissick shares the secrets to teaching yoga to children and young people with Autistic Spectrum Disorder (ASD). The physical, emotional and social benefits of yoga for autistic children can be profound, and this book will give you the confidence to get going with an array of fun activities and games from 'chasing the frog' to 'yoga detective'. Whether you work in special needs school, primary mainstream school or the community, or you are the parent of an autistic child, this book will equip you with plans, structures, goals, teaching tips and a multitude of real-life stories. The book is suitable for teaching everyone on the spectrum, with an emphasis on teaching those with more complicated needs. It is also relevant for use with children who have related needs such as ADHD and sensory processing challenges. Beautifully illustrated with images of the postures taught within, it is the perfect go-to resource for anyone interested in engaging children and young people in yoga.
Includes bibliographical references.
Keywords: Autistic children -- Health and hygiene; Autistic youth -- Health and hygiene; Hatha yoga for children -- Therapeutic use; Relaxatietechnieken ; yoga